Comparison of approaches to chondroprotective therapy based on the analysis of clinical recommendations from different countries - I. V. Samorodskaya; V. I. Stepchenkov (Медицинский совет, 2020)
Currently, with osteoarthritis (OA), numerous over-the-counter and prescription drugs are used, as well as biologically active additives (BAA). Significant market share in Russia are: chondroitin sulfate, glycosaminoglycan-peptide complex and Alflutop.The purpose of the article is to compare the clinical recommendations of the professional communities of doctors of the Russian Federation, countries of Europe, Great Britain, the USA, Canada, Australia on approaches to chondroprotective therapy/SYSADOA for osteoarthritis using the example of chondroitin sulfate, glycosamine glycan-peptide complex and Alflutop.Materials and methods: The analysis included 11 clinical recommendations (guideline) from 2008 to 2019 on the management of patients with OA.Results: The glycosaminoglycan-peptide complex (Rumalon) and Alflutop were recommended by the Russian Scientific Medical Society of Therapists (RNMOT), but are not mentioned in the recommendations of several Russian professional communities. In the European recommendations, the glycosaminoglycan-peptide complex and the drug Alflutop are not considered. Chondroitin sulfate to reduce the symptoms of OA is recommended by 5 professional guideline. With the exception of Russian recommendations, the listed professional communities recommend the use of chondroitin sulfate only as a “pharmaceutical quality drug”.Conclusion: It is advisable to agree on Russian recommendations on the use of the drugs in question. At the level of foreign and Russian professional communities, particular attention is required to analysis of data on the use of chondroitin sulfate, taking into account the quality of production, the composition of active substances and bioavailability, the quantitative content of active substances and the quality of substances. It is necessary to systematize the products with a separate assessment of the effectiveness of registered medicines, biologically active additives of pharmaceutical quality and low-quality products with minimal bioavailability.